1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Frank Modern Certificate Solution for Class 9 Mathematics Chapter 5 - Factorisation

Frank Textbook Solutions Chapter 5 - Factorisation

Frank Textbook Solutions are considered extremely helpful for solving difficult questions in the ICSE Class 9 Mathematics exam. TopperLearning Textbook Solutions are compiled by our subject experts. Herein, you can find all the answers to the questions of   Chapter 5 - Factorisation for the Frank textbook.

Frank Textbook Solutions for class 9  are in accordance with the latest ICSE syllabus, and they are amended from time to time to be most relevant. Our free Frank Textbook Solutions for ICSE Class 9 Mathematics will give you deeper insight on the chapters and will help you to score more marks in the final examination. ICSE Class 9 students can refer to our solutions while doing their homework and while preparing for the exam.

Exercise/Page

Frank Modern Certificate Solution for Class 9 Mathematics Chapter 5 - Factorisation Page/Excercise 5.1

Solution 1(a)

Solution 1(b)

Solution 1(c)

Solution 1(d)

Solution 1(e)

Solution 1(f)

Solution 1(g)

Solution 1(h)

Solution 1(i)

Solution 1(j)

Solution 1(k)

Solution 2(a)

15xy - 9x - 25y + 15

= (15xy - 9x) - (25y + 15)

= 3x(5y - 3) - 5(5y - 3)

= (5y - 3)(3x - 5)

Solution 2(b)

15x2 + 7y - 3x - 35xy

= 15x2 - 3x - 35xy + 7y

= (15x2 - 3x) - (35xy - 7y)

= 3x(5x - 1) - 7y(5x - 1)

= (5x - 1)(3x - 7y)

Solution 2(c)

9 + 3xy + x2y + 3x

= 9 + 3xy + 3x + x2y

= (9 + 3xy) + (3x + x2y)

= 3(3 + xy) + y(3 + xy)

= (3 + xy)(3 + x)

Solution 2(d)

8(2a + b)2 - 8a - 4b

= 8(2a + b)2 - (8a + 4b)

= 8(2a + b)2 - 4(2a + b)

= 4(2a + b)[2(2a + b) - 1]

= 4(2a + b)[4a + 2b - 1]

Solution 2(e)

x(x - 4) - x + 4

= x(x - 4) - 1(x - 4)

= (x - 4)(x - 1)

Solution 2(f)

2m3 - 5n2 - 5m2n + 2mn

= 2m3 + 2mn - 5m2n - 5n2

= (2m3 + 2mn) - (5m2n + 5n2)

= 2m(m2 + n) - 5n(m2 + n)

= (m2 + n)(2m - 5n)

Solution 2(g)

4abx2 + 49aby2 + 14xy(a2 + b2)

= 4abx2 + 49aby2 + 14a2xy + 14b2xy

= (4abx2 + 14a2xy) + (14b2xy + 49aby2)

= 2ax(2bx + 7ay) + 7by(2bx + 7ay)

= (2bx + 7ay)(2ax + 7by)

Solution 2(h)

9x3 + 6x2y2 - 4y3 - 6xy

= 9x3 + 6x2y2 - 6xy - 4y3

= (9x3 + 6x2y2) - (6xy + 4y3)

= 3x2(3x + 2y2) - 2y(3x + 2y2)

= (3x + 2y2)(3x2 - 2y)

Solution 2(i)

3ax2 - 5bx2 + 9az2 + 6ay2 - 10by2 - 15bz2

= 3ax2 + 6ay2 + 9az2 - 5bx2 - 10by2 - 15bz2

= (3ax2 + 6ay2 + 9az2) - (5bx2 + 10by2 + 15bz2)

= 3a(x2 + 2y2 + 3z2) - 5b(x2 + 2y2 + 3z2)

= (x2 + 2y2 + 3z2)(3a - 5b)

Solution 2(j)

8x3 - 24x2y + 54xy2 - 162y3

= (8x3 - 24x2y) + (54xy2 - 162y3)

= 8x2(x - 3y) + 54y2(x - 3y)

= (x - 3y)(8x2 + 54y2)

Solution 2(k)

2a + b + 3c - d + (2a + b)3 + (2a + b)2(3c - d)

= (2a + b + 3c - d) + [(2a + b)3 + (2a + b)2(3c - d)]

= 1(2a + b + 3c - d) + (2a + b)2(2a + b + 3c - d)

= (2a + b + 3c - d)[1 + (2a + b)2]

Solution 2(l)

xy(a2 + 1) + a(x2 + y2)

= a2xy + xy + ax2 + ay2

= (a2xy + ax2) + (ay2 + xy)

= ax(ay + x) + y(ay + x)

= (ay + x)(ax + y)

Solution 2(m)

p2x2 + (px2 + 1)x + p

= p2x2 + px3 + x + p

= (p2x2 + px3) + (p + x)

= px2(p + x) + 1(p + x)

= (p + x)(px2 + 1)

Solution 2(n)

x2 - (p + q)x + pq

= x2 - px - qx + pq

= (x2 - px) - (qx + pq)

= x(x - p) - q(x - p)

= (x - p)(x - q)

Solution 2(o)

Solution 2(p)

x + y + m(x + y)

= (x + y) + m(x + y)

= (x + y)(1 + m)

Solution 2(q)

Solution 2(r)

2p(a2 - 2b2) - 14p + (a2 - 2b2)2 - 7(a2 - 2b2)

= 2p(a2 - 2b2) + (a2 - 2b2)2 - 14p - 7(a2 - 2b2)

= [2p(a2 - 2b2) + (a2 - 2b2)2] - [14p + 7(a2 - 2b2)]

= (a2 - 2b2)(2p + a2 - 2b2) - 7(2p + a2 - 2b2)

= (2p + a2 - 2b2)(a2 - 2b2 - 7)

Frank Modern Certificate Solution for Class 9 Mathematics Chapter 5 - Factorisation Page/Excercise 5.2

Solution 1(a)

x2 + 6x + 8

= x2 + 4x + 2x + 8

= x(x + 4) + 2(x + 4)

= (x + 4)(x + 2)

Solution 1(b)

x2 - 11x + 24

= x2 - 8x - 3x + 24

= x(x - 8) - 3(x - 8)

= (x - 8)(x - 3)

Solution 1(c)

x2 + 5x - 6

= x2 + 6x - x - 6

= x(x + 6) - 1(x + 6)

= (x + 6)(x - 1)

Solution 1(d)

p2 - 12p - 64

= p2 - 16p + 4p - 64

= p(p - 16) + 4(p - 16)

= (p - 16)(p + 4)

Solution 1(e)

y2 - 2y - 24

= y2 - 6y + 4y - 24

= y(y - 6) + 4(y - 6)

=(y - 6)(y + 4)

Solution 1(f)

3x2 + 19x - 14

= 3x2 + 21x - 2x - 14

= 3x(x + 7) - 2(x + 7)

= (x + 7)(3x - 2)

Solution 1(g)

15a2 - 14a - 16

= 15a2 - 24a + 10a - 16

= 3a(5a - 8) + 2(5a - 8)

= (5a - 8)(3a + 2)

Solution 1(h)

12 + x - 6x2

= 12 + 9x - 8x - 6x2

= 3(4 + 3x) - 2x(4 + 3x)

= (4 + 3x)(3 - 2x)

Solution 1(i)

7x2 + 40x - 12

= 7x2 + 42x - 2x - 12

= 7x(x + 6) - 2(x + 6)

= (x + 6)(7x - 2)

Solution 2(a)

5x2 - 17xy + 6y2

= 5x2 - 15xy - 2xy + 6y2

= 5x(x - 3y) - 2y(x - 3y)

= (x - 3y)(5x - 2y)

Solution 2(b)

9x2 - 22xy + 8y2

= 9x2 - 18xy - 4xy + 8y2

= 9x(x - 2y) - 4y(x - 2y)

= (x - 2y)(9x - 4y)

Solution 2(c)

2x3 + 5x2y - 12xy2

= 2x3 + 8x2y - 3x2y - 12xy2

= 2x2(x + 4y) - 3xy(x + 4y)

= (x + 4y)(2x2 - 3xy)

= (x + 4y)x(2x - 3y)

= x(x + 4y)(2x - 3y)

Solution 2(d)

x2y2 + 15xy - 16

= x2y2 + 16xy - xy - 16

= xy(xy + 16) - 1(xy + 16)

= (xy + 16)(xy - 1)

Solution 2(e)

(2p + q)2 - 10p - 5q - 6

= (2p + q)2 - (10p - 5q) - 6

= (2p + q)2 - 5(2p + q) - 6

= (2p + q)2 - 6(2p + q) + (2p + q) - 6

= (2p + q)(2p + q - 6) + 1(2p + q - 6)

= (2p + q - 6)(2p + q + 1)

Solution 2(f)

y2 + 3y + 2 + by + 2b

= y2 + y + 2y + 2 + by + 2b

= y2 + y + by + 2y + 2 + 2b

= y(y + 1 + b) + 2(y + 1 + b)

= (y + 1 + b)(y + 2)

Solution 2(g)

x3y3 - 8x2y2 + 15xy

= x3y3 - 3x2y2 - 5x2y2 + 15xy

= x2y2(xy - 3) - 5xy(xy - 3)

= (xy - 3)(x2y2 - 5xy)

= (xy - 3)xy(xy - 5)

= xy(xy - 3)(xy - 5)

Solution 2(h)

Solution 2(i)

Solution 3(a)

5(3x + y)2 + 6(3x + y) - 8

= 5(3x + y)2 + 10(3x + y) - 4(3x + y) - 8

= 5(3x + y)(3x + y + 2) - 4(3x + y + 2)

= (3x + y + 2)[5(3x + y) - 4]

Solution 3(b)

5 - 4(a - b) - 12(a - b)2

= 5 - 10(a - b) + 6(a - b) - 12(a - b)2

= 5[1 - 2(a - b)] + 6(a - b)[1 - 2(a - b)]

= [5 + 6(a - b)][1 - 2(a - b)]

= (5 + 6a - 6b)(1 - 2a + 2b)

Solution 3(c)

(3a - 2b)2 + 3(3a - 2b) - 10

= (3a - 2b)2 + 5(3a - 2b) - 2(3a - 2b) - 10

= (3a - 2b)(3a - 2b + 5) - 2(3a - 2b +5)

= (3a - 2b + 5)((3a - 2b - 2)

Solution 3(d)

(a2 - 2a)2 - 23(a2 - 2a) + 120

= (a2 - 2a)2 - 15(a2 - 2a) - 8(a2 - 2a) + 120

= (a2 - 2a)(a2 - 2a - 15) - 8(a2 - 2a - 15)

= (a2 - 2a - 15)(a2 - 2a - 8)

= (a2 - 5a + 3a - 15)(a2 - 4a + 2a - 8)

= [a(a - 5) + 3(a - 5)][a(a - 4) + 2(a - 4)]

= [(a - 5)(a + 3)][(a - 4)(a + 2)]

= (a - 5)(a + 3)(a - 4)(a + 2)

= (a + 2)(a + 3)(a - 4)(a - 5)

Solution 3(e)

(x + 4)2 - 5xy - 20y - 6y2

= (x + 4)2 - 5y(x + 4) - 6y2

= (x + 4)2 - 6y(x + 4) + y(x + 4) - 6y2

= (x + 4)(x + 4 - 6y) + y(x + 4 - 6y)

= (x + 4 - 6y)(x + 4 + y)

= (x - 6y + 4)(x + y + 4)

Solution 3(f)

7(x - 2)2 - 13(x - 2) - 2

= 7(x - 2)2 - 14(x - 2) + (x - 2) - 2

= 7(x - 2)(x - 2 - 2) + 1(x - 2 - 2)

= 7(x - 2)(x - 4) + 1(x - 4)

= (x - 4)[7(x - 2) + 1]

= (x - 4)(7x - 14 + 1)

= (x - 4)(7x - 13)

Solution 3(g)

12 - (y + y2)(8 - y - y2)

= 12 - a(8 - a) [Taking y + y2 = a]

= 12 - 8a + a2

= 12 - 6a - 2a + a2

= 6(2 - a) - a(2 - a)

= (2 - a)(6 - a)

= [2 - (y + y2)][6 - (y + y2)]

= (2 - y - y2)(6 - y - y2)

= (2 - 2y + y - y2)(6 - 3y + 2y - y2)

= [2(1 - y) + y(1 - y)][3(2 - y) + y(2 - y)]

= [(1 - y)(2 + y)][(2 - y)(3 + y)]

= (1 - y)(2 + y)(2 - y)(3 + y)

= (y - 1)(y + 2)(y - 2)(y + 3)

Solution 3(h)

(p2 + p)2 - 8(p2 + p) + 12

= (p2 + p)2 - 6(p2 + p) - 2(p2 + p) + 12

= (p2 + p)(p2 + p - 6) - 2(p2 + p - 6)

= (p2 + p - 6)(p2 + p - 2)

= (p2 + 3p - 2p - 6)(p2 + 2p - p - 2)

= [p(p + 3) - 2(p + 3)][p(p + 2) - 1(p + 2)]

= [(p + 3)(p - 2)][(p + 2)(p - 1)]

= (p + 3)(p - 2)(p + 2)(p - 1)

Solution 4(a)

(y2 - 3y)(y2 - 3y + 7) + 10

= a(a + 7) + 10 [taking (y2 - 3y) = a]

= a2 + 7a + 10

= a2 + 5a + 2a + 10

= a(a + 5) + 2(a + 5)

= (a + 5)(a + 2)

= (y2 - 3y + 5)(y2 - 3y + 2)

= (y2 - 3y + 5)(y2 - 2y - y + 2)

= (y2 - 3y + 5)[y(y - 2) - 1(y - 2)]

= (y2 - 3y + 5)[(y - 2)(y - 1)]

= (y - 1)(y - 2)(y2 - 3y + 5)

Solution 4(b)

(t2 - t)(4t2 - 4t - 5) - 6

= (t2 - t)[4(t2 - t) - 5] - 6

= a[4a - 5] - 6 [Taking (t2 - t) = a]

= 4a2 - 5a - 6

= 4a2 - 8a + 3a - 6

= 4a(a - 2) + 3(a - 2)

= (a - 2)(4a + 3)

= (t2 - t - 2)[4(t2 - t) + 3]

= (t2 - 2t + t - 2)(4t2 - 4t + 3)

= [t(t - 2) + 1(t - 2)](4t2 - 4t + 3)

= [(t - 2)(t + 1)](4t2 - 4t + 3)

= (t + 1)(t - 2)(4t2 - 4t + 3)

Solution 4(c)

12(2x - 3y)2 - 1(2x - 3y) - 1

= 12a2 - a - 1 [Taking (2x - 3y) = a]

= 12a2 - 4a + 3a - 1

= 4a(3a - 1) + 1(3a - 1)

= (3a - 1)(4a + 1)

= [3(2x - 3y) - 1][4(2x - 3y) + 1]

= (6x - 9y - 1)(8x - 12y + 1)

Solution 4(d)

6 - 5x + 5y + (x - y)2

= 6 - 5(x - y) + (x - y)2

= 6 - 3(x - y) - 2(x - y) + (x - y)2

= 3[2 - (x - y)] - (x - y)[2 - (x - y)]

= 3(2 - x + y) - (x - y)(2 - x + y)

= (2 - x + y)(3 - x + y)

Solution 4(e)

Solution 4(f)

P4 + 23p2q2 + 90q4

= p4 + 18p2q2 + 5p2q2 + 90q4

= p2(p2 + 18q2) + 5q2(p2 + 18q2)

= (p2 + 18q2)(p2 + 5q2)

Solution 4(g)

2a3 + 5a2b - 12ab2

= 2a3 + 8a2b - 3a2b - 12ab2

= 2a2(a + 4b) - 3ab(a + 4b)

= (a + 4b)(2a2 - 3ab)

= (a + 4b)a(2a - 3b)

= a(a + 4b)(2a - 3b)

Frank Modern Certificate Solution for Class 9 Mathematics Chapter 5 - Factorisation Page/Excercise 5.3

Solution 1(a)

x2 - 16

= x2 - 42

= (x - 4)(x + 4)

Solution 1(b)

64x2 - 121y2

= (8x)2 - (11y)2

= (8x - 11y)(8x + 11y)

Solution 1(c)

441 - 81y2

= (21)2 - (9y)2

= (21 - 9y)(21 + 9y)

= 3(7 - 3y)3(7 + 3y)

= 9(7 - 3y)(7 + 3y)

Solution 1(d)

x6 - 196

= (x3)2 - (14)2

= (x3 - 14)(x3 + 14)

Solution 1(e)

625 - b2

= (25)2 - (b)2

= (25 - b)(25 + b)

Solution 1(f)

Solution 1(g)

8xy2 - 18x3

= 2x(4y2 - 9x2)

= 2x[(2y)2 - (3x)2]

= 2x[(2y - 3x)(2y + 3x)]

= 2x(2y - 3x)(2y + 3x)

Solution 1(h)

16a4 - 81b4

= (4a2)2 - (9b2)2

= (4a2 - 9b2)(4a2 + 9b2)

= [(2a)2 - (3b)2](4a2 + 9b2)

= [(2a - 3b)(2a + 3b)](4a2 + 9b2)

= (2a - 3b)(2a + 3b)(4a2 + 9b2)

Solution 1(i)

a(a - 1) - b(b - 1)

= a2 - a - b2 + b

= a2 - b2 - a + b

= (a2 - b2) - (a - b)

= (a - b)(a + b) - (a - b)

= (a - b)(a + b - 1)

Solution 1(j)

(x + y)2 - 1

= (x + y)2 - (1)2

= (x + y + 1)(x + y - 1)

Solution 1(k)

x2 + y2 - z2 - 2xy

= x2 + y2 - 2xy - z2

= (x2 + y2 - 2xy) - z2

= (x - y)2 - (z)2

= (x - y - z)(x - y + z)

Solution 1(l)

(x - 2y)2 - z2

= (x - 2y)2 - (z)2

= (x - 2y - z)(x - 2y + z)

Solution 2(a)

9(a - b)2 - (a + b)2

= [3(a - b)]2 - (a + b)2

= [3(a - b) - (a + b)][3(a - b) + (a + b)]

= (3a - 3b - a - b)(3a - 3b + a + b)

= (2a - 4b)(4a - 2b)

= 2(a - 2b)2(2a - b)

= 4(a - 2b)(2a - b)

Solution 2(b)

25(x - y)2 - 49(c - d)2

= [5(x - y)]2 - [7(c - d)]2

= [5(x - y) - 7(c - d)][5(x - y) + 7(c - d)]

= (5x - 5y - 7c + 7d)(5x - 5y + 7c - 7d)

Solution 2(c)

(2a - b)2 - 9(3c - d)2

= (2a - b)2 - [3(3c - d)]2

= [(2a - b) - 3(3c - d)][(2a - b) + 3(3c - d)]

= (2a - b - 9c + 3d)(2a - b + 9c - 3d)

Solution 2(d)

b2 - 2bc + c2 - a2

= (b2 - 2bc + c2) - a2

= (b - c)2 - (a)2

= (b - c - a)(b - c + a)

Solution 2(e)

Solution 2(f)

(x2 + y2 - z2)2 - 4x2y2

= (x2 + y2 - z2)2 - (2xy)2

= (x2 + y2 - z2 - 2xy)(x2 + y2 - z2 + 2xy)

= [(x2 + y2 - 2xy) - z2][(x2 + y2 + 2xy) - z2]

= [(x - y)2 - z2][(x + y)2 - z2]

= [(x - y - z)(x - y + z)][(x + y - z)(x + y + z)]

= (x - y - z)(x - y + z)(x + y - z)(x + y + z)

Solution 2(g)

a2 + b2 - c2 - d2 + 2ab - 2cd

= (a2 + b2 + 2ab) - (c2 + d2 + 2cd)

= (a + b)2 - (c + d)2

= (a + b + c + d)(a + b - c - d)

Solution 2(h)

4xy - x2 - 4y2 + z2

= z2 - x2 - 4y2 + 4xy

= z2 - (x2 + 4y2 - 4xy)

= z2 - (x - 2y)2

= [z - (x - 2y)][z + (x - 2y)]

= (z - x + 2y)(z + x - 2y)

Solution 2(i)

4x2 - 12ax - y2 - z2 - 2yz + 9a2

= (4x2 - 12ax + 9a2) - (y2 + z2 + 2yz)

= (2x - 3a)2 - (y + z)2

= [(2x - 3a) + (y + z)][(2x - 3a) - (y + z)]

= (2x - 3a + y + z)(2x - 3a - y - z)

Solution 2(j)

(x + y)3 - x - y

= (x + y)(x + y)2 - (x + y)

= (x + y)[(x + y)2 - 1]

= (x + y)[(x + y + 1)(x + y - 1)]

= (x + y)(x + y + 1)(x + y - 1)

Solution 2(k)

y4 + y2 + 1

= y4 + 2y2 + 1 - y2

= (y2 + 1)2 - y2

= (y2 + 1 + y)(y2 + 1 - y)

Solution 2(l)

(a2 - b2)(c2 - d2) - 4abcd

= a2c2 - a2d2 - b2c2 + b2d2 - 4abcd

= a2c2 + b2d2 - 2abcd - a2d2 - b2c2 - 2abcd

= (a2c2 + b2d2 - 2abcd) - (a2d2 + b2c2 + 2abcd)

= (ac - bd)2 - (ad + bc)2

= [(ac - bd) + (ad + bc)][(ac - bd) - (ad + bc)]

= (ac - bd + ad + bc)(ac - bd - ad - bc)

Solution 3(a)

Solution 3(b)

Solution 3(c)

Solution 4(a)

Solution 4(b)

Solution 4(c)

Solution 4(d)

Solution 4(e)

Solution 4(f)

Browse Study Material

Browse questions & answers

TopperLearning provides step-by-step solutions for each question in each chapter in the Frank textbook recommended by ICSE schools. Access Chapter 5 - Factorisation here. Our Frank Textbook Solutions for ICSE Class 9 Mathematics are designed by our subject matter experts. These solutions will help you to revise the whole chapter, so you can clear your fundamentals before the examination.

Text Book Solutions

ICSE IX - Mathematics

This content is available for subscribed users only.

OR

Call us

1800-212-7858 (Toll Free) to speak to our academic expert.
OR

Let us get in touch with you